1996
DOI: 10.1144/gsl.sp.1996.117.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and systems tract interpretation of the epicontinental Oligocene deposits in the Danish North Sea

Abstract: A sequence stratigraphical scheme has been established for the siliciclastic Cenozoic deposits in the southeastern North Sea Basin. The present paper addresses the problem of recognizing systems tracts by means of logs, using the Oligocene sequences as an example. The Oligocene sequences are characterized by an overall prograding seismic reflection pattern, and systems tracts cannot be interpreted from seismic sections alone.The sequences are dominated by marine clay deposits, and abrupt changes in lithologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…2), dominated by SW-ward prograding siliciclastic units, which are unconformably overlying the Eocene hemipelagic deposits (Michelsen et al, 1995(Michelsen et al, , 1998Schiøler et al, 2007) and reach over 1000 m of thickness. Michelsen and Danielsen (1996) and Danielsen et al (1997) showed that the Oligocene sediments originated from the north east, and that the depocenters of the individual sequences migrated westwards, parallel to the pinch-out line of the Zechstein salt and onto the northern flank of the Paleozoic Ringkøbing-Fyn High.…”
Section: Geological Settingmentioning
confidence: 99%
“…2), dominated by SW-ward prograding siliciclastic units, which are unconformably overlying the Eocene hemipelagic deposits (Michelsen et al, 1995(Michelsen et al, , 1998Schiøler et al, 2007) and reach over 1000 m of thickness. Michelsen and Danielsen (1996) and Danielsen et al (1997) showed that the Oligocene sediments originated from the north east, and that the depocenters of the individual sequences migrated westwards, parallel to the pinch-out line of the Zechstein salt and onto the northern flank of the Paleozoic Ringkøbing-Fyn High.…”
Section: Geological Settingmentioning
confidence: 99%
“…Sequence stratigraphic studies have shown that the Oligocene was characterized by south and southwestward progradation (Michelsen & Danielsen 1996;Danielsen et al 1997, Michelsen et al 1998). In the eastern North Sea area the progradational units generated an E-W striking palaeosiope with an overall dip towards the south during the Oligocene as outlined by the time-structure map in Figure 1.…”
mentioning
confidence: 99%
“…The previously used sequence stratigraphic subdivision (Michelsen et al, 1998;Michelsen and Danielsen, 1996;Danielsen et al, 1997) was primarily based on well log analysis supported by 2D seismic sections. However, the introduction of 3D seismics in sequence stratigraphic analysis calls for a revision of the subdivision.…”
Section: Stratigraphic Sequences and 3d Seismic Datamentioning
confidence: 99%
“…At this time the sedimentation of mainly hemipelagic clays of the Eocene was succeeded by prograding muddy and locally sandy sediments from Fennoscandia (Michelsen et al, 1998;Schiøler et al, 2007). The Oligocene clinoforms exceed 1 km in thickness in the Norwegian-Danish Basin (Schiøler et al, 2007) and are subdivided into a number of sequences showing progradation from the east e northeast (Michelsen and Danielsen, 1996;Danielsen et al, 1997). The structure and development of these sequences have been the subject of many sequence stratigraphic studies (Michelsen and Danielsen, 1996;Danielsen et al, 1997;Clausen et al, 1999Clausen et al, , 2000 but attempts to correlate the sequence development to glacioeustatic changes (Miller et al, 1991) have previously been hampered by the poor datings of the sequence boundaries (Clausen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%